P.098 The Epilepsy Surgery Experience in Children with Infantile Spasms at the Hospital for Sick Children. (November 2021) - Gettings, J; Shafi, S; Boyd, J; Snead, O; Rutka, J; Drake, J; McCoy, B; Whitney, R; Go, C
Abstract : Background: Infantile spasms (IS) is an epileptic encephalopathy, characterized by epileptic spasms, hypsarrhythmia, and developmental regression. This is a retrospective case series detailing the experience in children with IS who have undergone epilepsy surgery at The Hospital for Sick Children (HSC). Methods: Records of 223 patients from HSC were reviewed. Patients were included if they had a current or previous history of IS with a lesion detected on MRI/PET scan who underwent epilepsy surgery. Results: Nineteen patients were included. The etiology of IS was encephalomalacia in six patients (32%), malformations of cortical development in 11 patients (58%), atypical hypoglycaemic injury in one patient (0.5%), and partial hemimegalencephaly in one patient (0.5%). The median age at the onset of IS was five months. The median age at surgery was 18 months. Nine patients (47%) underwent hemispherectomy and 10 patients (53%) underwent lobectomy/lesionectomy. Fifteen patients (79%) were considered ILAE Seizure Outcome Class 1. Developmental outcome was improved in 14/19 (74%) and stable in 5/19 (26%) patients. Conclusions: Even with a generalized EEG pattern such as hypsarrhythmia, patients should be considered for focal resective surgery. Early surgical intervention shortens the duration of active epilepsy thus limiting the potentially irreversible effects of on-going seizures.